2012
DOI: 10.1038/ejhg.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric polymicrogyria and pachygyria associated with TUBB2B gene mutations

Abstract: The purpose of the study is to explore the causative role of TUBB2B gene mutations in patients with different malformations of cortical development. We collected and evaluated clinical and MRI data of a cohort of 128 consecutive patients (61 females and 67 males) in whom brain MRI had detected a spectrum of malformations of cortical development including polymicrogyria or pachygyria, who were mutation-negative to other possible causative genes. Mutation analysis of the TUBB2B gene was performed. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 12 publications
2
54
1
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19] Mutations in the TUBB2B gene have been associated with bilateral, asymmetrical PMG 20 and schizencephaly 21 as well as symmetrical PMG and pachygyria. 22,23 Axon guidance disorders (corpus callosum abnormalities and hypoplasia of the oculomotor nerves) and cortical malformations (PMG and gyral disorganization) have been found in individuals carrying defects in the TUBB3 gene. 24,25 Mutations in the TUBA8 gene have been associated with optic atrophy and bilateral PMG.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] Mutations in the TUBB2B gene have been associated with bilateral, asymmetrical PMG 20 and schizencephaly 21 as well as symmetrical PMG and pachygyria. 22,23 Axon guidance disorders (corpus callosum abnormalities and hypoplasia of the oculomotor nerves) and cortical malformations (PMG and gyral disorganization) have been found in individuals carrying defects in the TUBB3 gene. 24,25 Mutations in the TUBA8 gene have been associated with optic atrophy and bilateral PMG.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, neuropathological examination of a fetus showed absence of cortical lamination with ectopic neurons in the white matter and in the leptomeningeal spaces as a consequence of breaches in the pial basement membrane [153]. TUBB2B mutations were also identified in symmetric PMG and pachygyria, complex malformations of cortical development, and lissencephaly [176,180]. The analysis of somatic mutations performed by Jamuar and col. [39] in a cohort of 158 patients with MCDs, also found a patient with a pathogenic mutation in TUBB2B presenting frontal pachygyria, parietal, occipital and temporal PMG, a small dysplastic cerebellum, hypoplastic pons and hypoplastic optic nerves.…”
Section: 22a Tubulinopathiesmentioning
confidence: 99%
“…Recent work, however, has shown that all of the six grades of classic lissencephalies (Table 1) are caused by mutations of genes encoding tubulins ( primarily TUBA1A) (Poirier et al 2007) or proteins that function in conjunction with microtubules (microtubule-associated proteins or MAPs, such as DCX, LIS1, cytoplasmic dynein, kinesins, NudE) (Dobyns et al 1993;Gleeson et al 1998;Toyo-oka et al 2003;Lecourtois et al 2010;Cushion et al 2013;Poirier et al 2013). As mutations of genes encoding tubulins and MAPs are associated with, and likely responsible for, other MCDs (such as heterotopia and polymicrogyria [PMG]-like cortex) (Poirier et al , 2012Guerrini et al 2012;Cushion et al 2013), one might consider altering the classification to make malformations secondary to mutations of tubulin and MAP genes as a major category of MCD with classic lissencephalies as a subcategory. It will be interesting to determine what differences are seen in the mutations of genes coding for MAPs as compared with those coding for the tubulins themselves.…”
Section: Malformations Secondary To Tubulin and Microtubule-associatementioning
confidence: 99%
“…PMG is poorly understood from a brain developmental perspective, partly because the term has been used imprecisely in the literature, and partly because many different processes can result in a thin cortex with many small sulci/ gyri: shunted brains of infants born with severe congenital hydrocephalus (stenogyria) (Miller et al 2008), brains with defects in the PLM (cob-www.perspectivesinmedicine.org blestone cortical malformations) Devisme et al 2012), ciliopathies (Giordano et al 2009;Kheradmand Kia et al 2012), tubulinopathies (Jaglin et al 2009;Jansen et al 2011;Cederquist et al 2012;Guerrini et al 2012;Romaniello et al 2012), inborn errors of metabolism (Gressens et al 2000;van Straaten et al 2005), formation of subcortical heterotopia (Barkovich 2000), and many others. Although it has become accepted that stenogyria and cobblestone cortex differ from "true" PMG, the many different types of irregular cerebral cortices that continue to be labeled as PMG cause considerable confusion and have resulted in some investigators creating a category of "PMG-like" malformations (Cushion et al 2013).…”
Section: Pmgsmentioning
confidence: 99%